NA VOZ DE UMA MÃE: A ESCRITA DA MATERNIDADE NAS MEMÓRIAS DE JANE LAZARRE E RACHEL CUSK - SITTA, GABRIELA DAL BOSCO (2023)
This work discusses autobiographical writing about motherhood, focusing on the myth of motherly love (BADINTER, 1980). It analyzes two memoirs whose authors recount their experiences as mothers: The Mother Knot (1976) by American writer Jane Lazarre and A Life's Work: On Becoming a Mother (2001) by British-Canadian writer Rachel Cusk. For these writers, doubts, dissatisfactions, and anguish stemming from motherhood are the raw materials of writing, which is also motivated by the desire to narrate the transformation of a woman into a mother. By analyzing these books, we seek to characterize what we call the “storyteller mother”, a recurring instance in contemporary novels. We also aim to investigate how Cusk and Lazarre develop their positions towards their children through writing, memoiristic storytelling, and what Lazarre calls “the language of a mother's voice”. According to our hypothesis, the construction of these writers’identities as mothers occurs (also) through narrative. We attempt to reveal that the storyteller mothers depicted by Cusk and Lazarre do not recognize themselves as mothers simply by giving birth, as the myth of motherly love assumes. Instead, they develop their perspectives towards their children based on a narrative that deals with the ambivalent feelings they have for them.